PENGARUH KONSENTRASI GULA DAN CARBOXY METIL CELULOSA TERHADAP KARAKTERISTIK SIRUP KETELA RAMBAT UNGU (IPOMOEA BATATAS) - Selamet Duniaji, Agus; Anita Budiarti, I Gst Ngurah Agung (Agrotekno; Vol. 13, No. 1 Februari 2007)
Sweat potato can be processed to be several of food products. One of the products is sweat potato syrup, especially violet sweat potato which is including pigment anthocyanine. The objective of research was to know the effect of sugar concentration and carboxy methyl cellulosa (CMC) on the characteristic of sweat potato syrup. The experiment used randomized Complete design (RAL) with factorial block consist of sugar concentration 50, 60, 70 and 80% and adding carboxy methyl cellulose, 0, 0,5, 1,0 and 1,5%. Result of research showed that the adding of sugar concentration 60 percent and carboxy methyl cellulosa 1,5 percent produce the best characteristic of sweat potato syrup with criteria such as total soluble solid 75,60 % brix, viscosity 11,66 cp, vitamin C 0,44 mg/100g, anthocyanine content 11,15 mg/100g and total of fungi 50 Cfu/ml. All of characteristic as well as according to Indonesian standardization code (SNI-01- 3544-1994).
Keywords: sugar, carboxy methyl cellulosa, sweat potato and syrup